Using of the differential geometric methods for constructing the aircraft moving trajectories - V. K. Orlov; V. S. Ramadanov (Известия высших учебных заведений России: Радиоэлектроника, 2015)
A simple mathematical model of the aircraft flying to create test trajectories is used for modeling the various navigation systems is developed. The analysis of the known methods for trajectories producing is provided. A new method based on the motion modeling with the set parameters after equidistant above the surface of Earth ellipsoid is offered.